THE INFLUENCE OF INTERNAL CONTROL AND COMPENSATION ON EMPLOYEE PERFORMANCE AT CV. ARJUNA PERSADA GEMILANG SOUTH TANGERANG - Candra Natawijaya; Muhammad Arief Noor; Tuti Herawati; Cinta Rahmi; Ahmad Khatimi; Yayah Nihayah (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2023)
The Influence of Internal Control and Compensation on Employee Performance at CV. Arjuna Persada Gemilang South Tangerang. Under the Guidance of Dr. Muhammad Ramdhan, MM and Dr. Ir. H. Rachman Upe, MM. The purpose of this research is to determine (1) the effect of internal recognition on employee performance at CV Arjuna Persada Gemilang partially, (2) the effect of compensation on employee performance at CV Arjuna Persada Gemilang partially (3) the effect of internal recognition and compensation on employee performance at CV Arjuna Persada Gemilang. The research method used is a quantitative research method. In this research, the samples taken were all CV employees. Arjuna Persada Gemilang, numbering 50 people. The sampling technique uses a sample method using a saturated sample method. The research results show that (1) Internal Control has a significant influence on Employee Performance at CV. Arjuna Persada Gemilang South Tangerang, (2) Compensation has a significant influence on employee performance at CV. Arjuna Persada Gemilang South Tangerang, (3) Internal Control and Compensation have a significant influence on Employee Performance at CV. Arjuna Persada Gemilang South Tangerang.